Co-composted Biochar Enhances Growth, Physiological, and Phytostabilization Efficiency of Brassica napus and Reduces Associated Health Risks Under Chromium Stress - Naveed, Muhammad; Tanvir, Bisma; Xiukang, Wang; Brtnicky, Martin; Ditta, Allah; Kucerik, Jiri; Subhani, Zinayyera; Nazir, Muhammad Zubair; Radziemska, Maja; Saeed, Qudsia; Mustafa, Adnan (Frontiers in Plant Science, 2021)
Among heavy metals, chromium (Cr) contamination is increasing day by day due to the use of un-treated industrial effluents for irrigation purposes and hence pose a severe threat to crop production. The present study evaluated the potential of compost, biochar, and co-composted biochar on growth, physiological, biochemical attributes, and health risks associated with the consumption of Brassica grown on Cr contaminated soil. Results revealed that, Cr stress (Cr-25) significantly reduced growth and physiological attributes and increased antioxidant enzyme activities in Brassica, but the applied amendments considerably retrieved the negative effects of Cr toxicity through improving the growth and physiology of plants. The maximum increase in plant height (75.3%), root length (151.0%), shoot dry weight (139.4%), root dry weight (158.5%), and photosynthetic rate (151.0%) was noted with the application of co-composted biochar under Cr stress (Cr-25) in comparison to control. Co-composted biochar application significantly reduced antioxidant enzyme activities i.e., APX (42.5%), GP (45.1%), CAT (45.4%), GST (47.8%), GR (47.1%) and RG (48.2%) as compared to control under Cr stress. The same treatment reduced the accumulation of Cr in grain, shoot, and roots of brassica by 4.12, 2.27, and 2.17 times and enhanced accumulation in soil by 1.52 times as compared to control. Moreover, the application of co-composted biochar significantly enhanced phytostabilization efficiency and reduced associated health risks with the consumption of brassica. It is concluded that the application of co-composted biochar in Cr contaminated soil can significantly enhance the growth, physiological and biochemical attributes of brassica, through reducing its uptake in plants and enhanced phytostabilization efficiency.